2019
DOI: 10.1016/j.actamat.2019.09.056
|View full text |Cite
|
Sign up to set email alerts
|

On the high creep strength of the W containing IRIS-TiAl alloy at 850 °C

Abstract: This paper presents a study of the creep at 850°C under 150 MPa of the IRIS alloy (Ti-Al48-W2-B0.1) densified by spark plasma sintering. The dislocation microstructure in a sample strained up to 1.5% was studied by post-mortem transmission electron microscopy. The deformation is mainly due to ordinary dislocations. Several populations of dislocations are evidenced. Their Burgers vectors, the plane in which they are moving and the corresponding deformation mechanisms are determined. In the discussion section, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 35 publications
5
11
0
Order By: Relevance
“…In the author's opinion, the interpretation of these ageing effects requires deep understanding of the microstructure evolutions versus ageing time and of the deformation mechanisms activated under the various applied solicitations. The deformation mechanisms activated at room and high temperatures in the SPS-IRIS alloy have been investigated elsewhere by the present authors [9,35]. Indeed, it has been shown that, at high temperatures, the interaction between dislocations moving by glide or climb processes and atoms of tungsten is the controlling phenomenon for the alloy strength.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In the author's opinion, the interpretation of these ageing effects requires deep understanding of the microstructure evolutions versus ageing time and of the deformation mechanisms activated under the various applied solicitations. The deformation mechanisms activated at room and high temperatures in the SPS-IRIS alloy have been investigated elsewhere by the present authors [9,35]. Indeed, it has been shown that, at high temperatures, the interaction between dislocations moving by glide or climb processes and atoms of tungsten is the controlling phenomenon for the alloy strength.…”
Section: Discussionmentioning
confidence: 73%
“…A significant part of the ductility loss measured in the aged alloy (0.22 %) could be attributed to the increase of the mean free path between obstacles for twins in the  phase with the reduced size of lamellar areas: the longer this distance, the larger the number of piledup twin dislocations at given stress, the higher the associated internal stress leading to the sample failure. At 800°C under high strain rate, the deformation results from the glide of ordinary dislocations controlled by a frictional force enhanced by the interaction between dislocations and tungsten atoms and from the crossing of / and /2 interfaces by the mobile dislocations [35]. Here again, the diminution of the interface number through that of the lamellar zones should slightly reduce the alloy strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Refractory metals such as W with a low diffusivity in TiAl alloys can significantly increase mechanical properties and corrosion resistance at elevated temperatures [ 7 ]. Alloying with W reduces dislocation mobility and increases the thermal stability of lamellar microstructure, which leads to an increase in creep resistance [ 8 , 9 , 10 , 11 , 12 , 13 ]. The positive influence of carbon on the creep strength of TiAl-based alloys has been published by several authors [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the presence of 0 phase in the final microstructure, which is unfavourable at high temperatures and brittle at room temperature, is avoided while the presence of  phase is promoted. The challenge is to have a homogeneous distribution of W atoms in the  phase to ensure a homogeneous structural hardening of that phase and the alloy via the interaction of W atoms with dislocations moving by various deformation mechanisms [6].…”
Section: Introductionmentioning
confidence: 99%